Key performance indicators of all-star player and winning teams in elite water polo at the 2020 Olympic Games - Ordonez, E. G.; Gonzalez, C. T. (International Journal of Performance Analysis in Sport, 2022)
The aim of this study was (i) to identify the key performance indicators that discriminate all-star from non-all-stars players, and (ii) to differentiate winning from drawing/losing teams during the men´s water polo Olympic Games (Tokyo, 2020). The sample consisted of all matches (n = 42) played by 12 teams (156 players). Differences were calculated using the Mann-Whitney U and student-t tests and the binary logistic regression. Minutes per match, goals, action goals, centre goals, extra-player goals, 6-m goals, penalty goals, steals and rebounds discriminated all-star from non-all-star players. However, only minutes per match (OR: 1.105), extra player goals (OR: 1.748), 6-m goals (OR = 3.617) and penalty goals (OR: 2.592) per time played were determined to differentiate all-star players. Regarding the second aim, the following variables discriminated winning from losing/drawing teams: % action goals, % 6-m goals, % penalty goals, team fouls, sprints won, steals and % goalkeeper actions shots. However, only % action goals (OR: 1.153), steals (OR: 1.279) and % action shots (OR: 1.093) predicted the match outcome. Coaching staffs may apply this information to different players, while account for individual differences and functional variability, to optimise practice planning and, consequently, the game performance of individuals and teams.